Humiliation : mental health and public shame - Svindseth, Marit F.; Crawford, Paul (Emerald points., 2019)
There is a global appetite to humiliate or publicly shame others and this has even become a source of entertainment for many. The growth and all-encompassing influence of social media has made the phenomenon of humiliation even more apparent and possible. This book examines the damaging impact of humiliation in human society. The relationship between humiliation and shame is explored in depth with a particular focus on the way this relationship affects people's self-image, self-esteem and memory. By using case studies of observed humiliation, the book discusses the power play between individuals, groups, organizations and nations. It shows how public shame can lead to damaging psychological states and violent responses amongst vulnerable people. This topical book presents an important and timely discussion for today's world, not least in showing the links between humiliation, terrorism and poor mental health.By offering strategies for responding to feelings of humiliation in a range of contexts, this book will prove a valuable resource for professionals concerned with mental health, public health, education and social care. Importantly, this is a book for all those affected by humiliation who want to take action and find new solutions for dealing with it.